A Giant Parasitic Leiomyoma with Blood Supply from Omental Branches: A Case Report - Mustafa Ulubay; Fahri Burçin Fıratlıgil; Uğur Keskin; Ulaş Fidan; Nuri Yiğit; Rıza Efendi Karaca; Ali Ergün (Gynecology Obstetrics & Reproductive Medicine)
A female patient with the age of 33 having gravida: 3, parity: 2 and D&C: 1, applied to our clinics by pelvic mass that she had. It had been comprehended from the anamnesis of the patient that she applied to a gynecologist because of ongoing inguinal pain and abdominal distension for about 4 months. In the physical examination, a mass that can be palpated in suprapubic region was observed. In transvaginal ultrasonographic examination, a giant leiomyom was determined having the dimensions of 9.5cm x 8.5 cm that was located at fundal uterus with subserous component and enlarged the uterus. Pfannenstiel incision was performed. In intraoperative examination, a fundal subserous located parasitic leiomyoma with around 10 cm diameter, supplied by a vascular structure about 30 cm in length from omentum was diagnosed.It was diagnosed that omentum adhered to leiomyoma partially. Firstly, omentum with its vascular structure was excised. Partial omentectomy was performed. Then, leiomyoma was excised by performing dissection and operation was ended up. Parasitic myomas are indicated as rarely seen myomas in literature. It is crucial to maintain specific diagnosis, careful imaging and serious planning in preoperative preparations.Although parasitic leiomyomas are rarely seen cases, because of abnormal vascularization and adhesion to other organs, one should be careful in preoperative examinations and sufficient blood supply should be maintained in case of bleeding. Additionally, surgical information has to be had for surgical exploration and pelvic anatomy.